Comparison of preoperative evaluation of malignant low-level biliary obstruction using plain magnetic resonance and coronal liver acquisition with volume acceleration technique alone and in combination. Issue 1 (December 2015) - Sun, Nana; Xu, Qing; Liu, Xisheng; Liu, Wei; Wang, Jianwei
Abstract Background To evaluate the clinical value of plain magnetic resonance (MR) imaging (including magnetic resonance cholangiopancreatography, MRCP) and coronal liver acquisition with volume acceleration (LAVA) technique in the diagnosis and preoperative assessment of malignant low-level biliary obstruction. Methods Forty-one patients with confirmed malignant low-level biliary obstruction were examined by plain MR, MRCP and coronal LAVA techniques. Group 1, plain MR (including MRCP); group 2, coronal LAVA; group 3, plain MR and coronal LAVA. Assessments included positioning, qualitative diagnosis and preoperative evaluation. The results were compared with pathological, endoscopic retrograde cholangiopancreatography or percutaneous transhepatic cholangiography results. Results There were 14 pancreatic adenocarcinoma, 12 distal common bile duct carcinoma, 10 ampullary carcinoma, and 5 duodenal carcinoma cases. There was no significant difference in accuracy of the three groups' positioning diagnoses, 87.8, 90.2, and 92.7 %, respectively. The accuracy of the qualitative diagnoses was lower in group 1 at 78.0 %, but not significantly different in groups 2 and 3 at 92.7 and 95.1 %, respectively (P  = 0.031, and 0.039, group 1 vs groups 2 and 3, respectively). Thirty-three patients underwent open surgery. There were 19 adjacent organ involvements, 9 vascular involvements, 13 lymph node metastases and 6 liver metastases. 22 patients were verified surgically and histologically for resectable lesions. Plain MR with coronal LAVA imaging showed 85.4 % accuracy, 90.9 % sensitivity, 78.9 % specificity, 83.3 % positive and 88.2 % negative predictive value for resectability. Conclusions Plain MR and coronal LAVA techniques are potential noninvasive tools for diagnosis and preoperative assessment of malignant low-level biliary obstruction.